2013
DOI: 10.1007/978-3-642-41914-0_32
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Plants in 3D from a Single Image Using Analysis-by-Synthesis

Abstract: Abstract. Mature computer vision techniques allow the reconstruction of challenging 3D objects from images. However, due to high complexity of plant topology, dedicated methods for generating 3D plant models must be devised. We propose to generate a 3D model of a plant, using an analysis-by-synthesis method mixing information from a single image and a priori knowledge of the plant species. First, our dedicated skeletonisation algorithm generates a possible branching structure from the foliage segmentation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…These approaches have been further extended to include single-image-based methods (Argudo et al 2016) to provide a more plausible appearance. Guénard et al (2013) used the analysis-bysynthesis strategy; they first reconstructed the initial skeletons using skeletonization and then refined the underlying parameters of branching systems to fit the observed silhouette. A recent method by Liu et al (2021) uses a generative adversarial network (GAN) to create 3D tree models from a single image.…”
Section: Plant/tree Structure From a Single 2d Imagementioning
confidence: 99%
“…These approaches have been further extended to include single-image-based methods (Argudo et al 2016) to provide a more plausible appearance. Guénard et al (2013) used the analysis-bysynthesis strategy; they first reconstructed the initial skeletons using skeletonization and then refined the underlying parameters of branching systems to fit the observed silhouette. A recent method by Liu et al (2021) uses a generative adversarial network (GAN) to create 3D tree models from a single image.…”
Section: Plant/tree Structure From a Single 2d Imagementioning
confidence: 99%
“…The initial skeleton is extended into the crown by iteratively substituting an existing branch by a subtree from a database. Guenard et al [GMBC13], on the other hand, extract the foliage and compute a vector field from the segmented shape that is used to obtain a skeleton. This base skeleton is populated by leaves and branchlets via an L-system.…”
Section: Tree Generation From Contoursmentioning
confidence: 99%
“…Subsequently, 2D strokes are employed to direct the synthesis of a 3D tree through a growth engine. Guénard et al suggested creating a 3D plant model through an analysis-by-synthesis approach, combining data from a single image with a priori knowledge of the plant species [18].…”
Section: Introductionmentioning
confidence: 99%